Thermodynamic solubility modeling, solvent effect and preferential solvation of curcumin in aqueous co-solvent mixtures of ethanol, n-propanol, isopropanol and propylene glycol. (April 2019) - Shen, Yingzhuo; Farajtabar, Ali; Xu, Jie; Wang, Jiali; Xia, Yuanyuan; Zhao, Hongkun; Xu, Renjie
Graphical abstract: Highlights: Curcumin solubility in four co-solvent mixtures was determined and correlated. Preferential solvation parameters were derived by IKBI method. Solute-solvent and solvent-solvent interactions were investigated using KAT-LSER model. Abstract: The equilibrium solubility of curcumin in solvent mixtures of ethanol (1) + water (2), n-propanol (1) + water (2), isopropanol (1) + water (2) and propylene glycol (PG, 1) + water (2) was determined experimentally by using saturation shake-flask method within the temperature range from (278.15 to 318.15) K under atmospheric pressure (101.1 kPa). At the same temperature and mass fraction of ethanol ( n -propanol, isopropanol or PG), the mole fraction solubility of curcumin was greater in ( n -propanol + water) than in the other three co-solvent mixtures. The solid phase was tested by X-ray power diffraction, which showed that no polymorphic transformation, solvate formation or crystal transition during entire experiments. Linear solvation energy relationship in terms of the solvent polarity parameters was used to study of the solvent effect on the mole fraction solubility. The preferential solvation parameters were derived from their thermodynamic solution properties by means of the inverse Kirkwood–Buff integrals. The preferential solvation parameters for ethanol, n -propanol, isopropanol or PG were positive in the four co-solvent mixtures in intermediate and co-solvent-rich compositions, which indicated that curcumin was preferentially solvated by co-solvent. It could act mainly as a Lewis acid interacting with proton-acceptor functional groups of the co-solvents. Temperature had a little effect on the preferential solvation magnitudes for the n -propanol and PG mixtures. In addition, the drugs' solubilities were mathematically represented by using the Jouyban-Acree model obtaining average relative deviations lower than 0.19% for correlative studies.